Cast from the herd memories of matriarchal Malaysia - M. Bakri Musa (ZI Publications Sendirian Berhad, 2016)
Cast from the herd: memories of matriarchal Malaysia chronicles the author's childhood in the world's largest matriarchial community, the Minangkabau, during the time when the country was transiting from its agrarian feudal roots to an urban democratic society, and in the background of a violent communist insurgency. This memoir gives a ground-level view of Malaysia's many tranformational events, from the Japanese Occupation, the brief but equally brutal three-week Chinese Communist rule that continued on as an extended guerilla warfare euphemistically referred to as The Emergency, the country's first election that led to its independece in 1957, and the nation's later merger with the other Bristish colonies in the region. On a personal level, it relates the writer's struggle to secure a secular English education amidst the intense nationalism and religious fervor of the period. The memoir ends with the author's first day on campus in Canada, and the attendant culture shock.